Peranan Pelatihan, Lingkungan Kerja dan Kompensasi terhadap Kinerja Karyawan - Yusup Adriyanto; Qodariah Qodariah (CV. Syntax Corporation Indonesia, 2022)
The purpose of this study is for the author to get an idea of whether the Role of Training, Work Environment, and Compensation in PT. Sanken Argadwija affects the performance of its employees. It is hoped that with this research the company can establish a strategy to improve the condition of the company and can improve the performance of its employees. Companies can also take competitive actions to always strive to improve the performance of their employees in a more sustainable manner. The research method used is a qualitative descriptive approach, data collection techniques are observation, interviews and documentation. The data analysis technique uses Miles and Huberman's interactive analysis model, namely data reduction, data presentation and conclusion drawing or verification. The results showed that Education/job training, improving working methods, wages/salaries according to work weight and performance, environmental improvements, working conditions, and motivation greatly affect employee productivity levels. Human factors consisting of factors: training, leadership, wage levels of workers, job satisfaction, incentives, profit sharing, work relations between colleagues, and absenteeism are also very decisive in employee performance.